Chlorate/Fe‐Bearing Phase Mixtures as a Possible Source of Oxygen and Chlorine Detected by the Sample Analysis at Mars Instrument in Gale Crater, Mars. Issue 11 (5th November 2018) - Hogancamp, J. V.; Sutter, B.; Morris, R. V.; Archer, P. D.; Ming, D. W.; Rampe, E. B.; Mahaffy, P.; Navarro‐Gonzalez, R.
Abstract: Oxygen and HCl gas releases detected by the Sample Analysis at Mars (SAM) instrument on board the Mars Science Laboratory Curiosity rover in several Gale Crater samples have been attributed to the thermal decomposition of perchlorates and/or chlorates. Previous experimental studies of perchlorates mixed with Fe‐bearing phases explained some but not all of the evolved oxygen releases and cannot explain the HCl releases. The objective of this paper was to evaluate the oxygen and HCl releases of chlorates and chlorate/Fe phase mixtures in experimental studies and SAM evolved gas analysis data sets. Potassium, magnesium, and sodium chlorate were independently mixed with hematite, magnetite, ferrihydrite, and palagonite and analyzed in a thermal evolved gas analyzer configured to operate similarly to the SAM instrument. Fe phases depressed the chlorate decomposition temperature 3–214 °C and consumed up to 75% of the evolved oxygen from chlorate decomposition. Chlorate/Fe phase mixtures have oxygen and HCl releases consistent with some samples analyzed by SAM. Reported oxychlorine abundances based on calculations using oxygen detected by SAM could be minimum values because Fe phases consume evolved oxygen. The results of this work demonstrate that chlorates could be present in the Martian soil and that oxygen and HCl release temperatures could be used to constrain which chlorate cation species are present in samples analyzed by SAM. Knowledge of which chlorates may be present in Gale Crater creates a better understanding of the detectability of organics by evolved gas analysis, habitability potential, and the chlorine cycle on Mars. Plain Language Summary: The Sample Analysis at Mars (SAM) instrument on board the Curiosity rover heats Martian soil and then detects the gases produced from the breakdown of chemicals. The SAM instrument has detected oxygen and hydrochloric acid (HCl) gas in several Gale Crater samples, which have been attributed to perchlorates (ClO4 − ) and/or chlorates (ClO3 − ). In this study, we mixed chlorates with iron minerals that exist on Mars (e.g., hematite). These mixtures and pure chlorates were analyzed in a SAM‐like laboratory instrument. Oxygen and HCl gas releases were compared to SAM data sets. Iron minerals decreased the chlorate breakdown temperature and the amount of oxygen produced. Chlorate/iron mineral mixtures have oxygen and HCl releases consistent with some samples analyzed by SAM. Reported perchlorate/chlorate abundances based on calculations using oxygen detected by SAM could be minimum values because iron minerals decrease the amount of oxygen produced from chlorates. These results demonstrate that chlorates could be present on Mars and that oxygen and HCl release temperatures could be used to constrain which type of chlorates are present in SAM samples. Knowledge of which chlorates may be present in Gale Crater creates a better understanding of the detectability of organic material by SAM, habitability potential, and the chlorine cycle on Mars. Key Points: Fe‐bearing phases catalyze the thermal decomposition of chlorates Fe‐bearing phases consume oxygen during thermal decomposition of chlorates Chlorates may be present in rocks and soils in Gale Crater